PARTISIPASI MASYARAKAT PESISIR TERHADAP KELESTARIAN HUTAN MANGROVE (Studi Kasus Di Desa Kuala Tambangan Kecamatan Takisung Kabupaten Tanah Laut) - Nurul Huda Safitri; Taufik Hidayat; Rizmi Yunita; Eny Dwi Pujawati (Universitas Lambung Mangkurat, 2012)
The research was implemented in the village of Kuala Tambangan Takisung District Tanah Laut Regency. Specifically this study aims: 1). Analyze the level of community participation in conservation of coastal mangrove forests, 2). Analyze the factors related to personal participation in the preservation of mangrove forests. The variables observed were: age, education level, income, occupation, activity and participation level in the organization with the indicator; participation in the planning phase, implementation phase and monitoring phase. To see the factors that influence personal participation rates used in analysis of serial correlation (r ser), to know the correlation of community participation with the age, education and income. Using analysis of contingency coefficient (KK), for measurements with the nominal scale is occupation and the ordinal scale is community participation and Spearman correlation analysis (rs), to measure whether or not the relationship between the two ordinal variables that activity within the organization means that rs is a measure of the level/degree of relationship between two ordinal data. The participation rate with 84 respondents coastal village of Kuala Tambang communities in the preservation of mangrove forests by 42 %, as the stage level of participation at this stage of planning, implementation, and monitoring is low amounting to between 20-50%. There is a significant relationship between personal factors that work with a very significant level of participation by the contingency coefficient (KK) = 0.63%. Activity in the organization with the level of participation by the coefficient spearman = 0.60. Education with a significant level of participation by the serial correlation = 0.42. Revenue by a significant level of the participation by the serial correlation = 0.26.